Utilizing poxviral vectored vaccines for antibody induction-progress and prospects. - Draper, S; Cottingham, MG; Gilbert, S (2013)
Over the last decade, poxviral vectors emerged as a mainstay approach for the induction of T cell-mediated immunity by vaccination, and their suitability for human use has led to widespread clinical testing of candidate vectors against infectious intracellular pathogens and cancer. In contrast, poxviruses have been widely perceived in the vaccine field as a poor choice of vector for the induction of humoral immunity. However, a growing body of data, from both animal models and recent clinical trials, now suggests that these vectors can be successfully utilized to prime and boost B cells and effective antibody responses. Significant progress has been made in the context of heterologous prime-boost immunization regimes, whereby poxviruses are able to boost responses primed by other vectors, leading to the induction of high-titre antigen-specific antibody responses. In other cases, poxviral vectors have been shown to stimulate humoral immunity against both themselves and encoded transgenes, in particular viral surface proteins such as influenza haemagglutinin. In the veterinary field, recombinant poxviral vectors have made a significant impact with numerous vectors licensed for use against a variety of animal viruses. On-going studies continue to explore the potential of poxviral vectors to modulate qualitative aspects of the humoral response, as well as their amenability to adjuvantation seeking to improve quantitative antibody immunogenicity. Nevertheless, the underlying mechanisms of B cell induction by recombinant poxviruses remain poorly defined, and further work is necessary to help guide the rational optimization of future poxviral vaccine candidates aiming to induce antibodies.